FAKTOR – FAKTOR YANG MEMENGARUHI MANAJEMEN LABA - Vera Veronica; Ferry Suhardjo (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study was to obtain empirical evidence of the effect of corporate governance, firm characteristics, and leverage on earnings management. The independent variables in this study are managerial ownership, institutional ownership, board of commissioners size, board of commissioners meeting, audit committee size, audit committee meeting, company size, leverage, and independent board of commissioners. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018 to 2020. The sample used in this study is 216 company data using the purposive sampling method. This study uses SPSS version 25 in data processing. This study uses multiple regression method to determine the effect of the independent variables on the dependent variable. The results of this study indicate that the variable size of the board of commissioners has a negative effect on earnings management and the leverage variable has a positive effect on earnings management. Meanwhile, the variables of managerial ownership, institutional ownership, board of commissioners meetings, audit committee size, audit committee meetings, company size, and independent board of commissioners meetings have no effect on earnings management.